Characterization of Differentially Expressed Transcripts of Oil Palm (Elaeis Guineensis Jacq.) Suspension Cells - Roowi, Siti Habsah (2009)

(untitled)
Oil palm tissue culture through somatic embryogenesis remains a problem because the production cost is still high and the process is very labour-intensive. The average callogenesis rate per ortet is only 20% with embryogenesis rate averages 6%. In this study, oil palm suspension cultures were initiated by transferring the gel-like friable embryogenic tissue onto liquid medium supplemented with auxin(s). The aim of this study was to understand and identify the underlying factors that are involved in the induction of somatic embryo through suspension cells cultured in different auxin(s) concentrations. Transcripts that were differentially expressed in oil palm suspension cells cultured at different auxin(s) were examined by using suppression subtractive hybridization (SSH). The four different hormone combinations examined were: T1 (0.1 mg/l 2,4-D and 1 mg/l NAA), T2 (0.4 mg/l 2,4-D and 1 mg/l NAA), T3 ( 1 mg/l NAA) and T4(0.4 mg/l 2,4-D). The first and second subtractions were performed using samples T1 and T2 in forward and reverse order. The other two subtractions were forward and reverse subtractions of T3 and T4, respectively. A total of 2019 cDNAs were cloned and isolated from these SSH libraries. Reverse northern analyses showed that 82 clones were isolated from library 1, 64 clones from library 2, 72 clones from library 3 and 76 clones from library 4. Among the 294 cDNA clones that were sequenced, 61 contigs (assembled from 165 sequences) and 129 singletons were obtained. Among the 61 contigs, 10 contigs consisted of sequences from treatment T1, 8 contigs from treatment T2, 10 contigs from treatment T3 and 13 contigs contain sequences from treatment T4, respectively. Northern analyses of 5 transcripts that were shown to be differentially expressed by reverse northern analysis revealed that transcripts 16A1 (a putative lignostilbene-α,β dioxygenase, EgLSD) and 16H12 (a putative ethylene responsive 6, EgER6) were differentially expressed in oil palm suspension cells treated with different levels of auxin. The full length cDNA sequence of EgLSD is 1801 bp with 58 bp of 5’ untranslated region and 119 bp of 3’ non coding region. The full length cDNA sequence of EgER6 is 810 bp with 120 bp of 5’ untranslated region and 88 bp of 3’ non coding region. The gene expression of these two candidates was further monitored by real-time quantitative RT-PCR. The transcripts of EgLSD were present throughout cell maturation from 0 day to 25 days with higher increase in ABA treated samples compared to the control without ABA treatment. On the other hand, the transcript level of EgER6 decreased drastically from 1 to 0.0001 for ABA treated samples. The results showed that these two genes respond to ABA during maturation stage in oil palm suspension cultures. The current finding showed that there is a crosstalk between ABA and Ethylene, whereby sugar acts as a switch to control the expression of EgLSD and EgER6. These genes can be used as a marker for somatic embryogenesis of oil palm through cell suspension culture.